Cesare Cases e Primo Levi - Cavaglion, Alberto (L’ospite ingrato, 2024)
From the first review (1947) to the writings published after the death of Primo Levi (1987) Cesare Cases followed the entire narrative journey of the author of If This Is a Man, with a constancy and sensitivity that have no equal and surprise in a critic known for his severity, often harsh even towards friends. The report examines everything that Cases wrote about Levi over the course of about half a century, trying to identify the salient points of what today appears to be a long defensive harangue against his detractors and against an academic world that took a long time to realize the greatness of Primo Levi.